Ultimate behaviour and serviceability analysis of stainless steel reinforced concrete beams. (1st December 2021) - Rabi, Musab; Cashell, K.A.; Shamass, Rabee
Highlights: The behaviour of stainless steel reinforced concrete beams is investigated. A full and simplified version of a deformation-based design method is proposed and examined herein with reference to the current design rules in Eurocode 2. A comprehensive parametric study is conducted to study the most influential parameters. The serviceability limit state is also explored through a detailed analysis of the deflection behaviour. Abstract: Stainless steel reinforcement has become a very attractive option for reinforced concrete structures owing to its distinctive properties including outstanding corrosion resistance, excellent fire behaviour, long life cycle as well as low maintenance requirements. Additionally, stainless steel reinforcement offers exceptional ductility and strain hardening characteristics compared with other common materials, which are very desirable in design to avoid sudden collapse. However, most global design standards do not incorporate an appropriate design approach for reinforced concrete members with stainless steel. The substantial strain hardening characteristics of stainless steel are typically not represented in standardised material models and therefore this attractive characteristic is not exploited in design resulting in structural and economic inefficiencies. Hence, the aim of this paper is to propose and validate a new deformation-based design approach for stainless steel reinforced concrete beams based on the continuous strength method, with reference to the current design rules provided in Eurocode 2. This approach is shown to be an effective design tool that exploits the distinctive characteristics of stainless steel reinforcement in an efficient and reliable manner. It is shown to provide a more efficient design with less over-conservatism and greater accuracy, compared with other methods. A comprehensive parametric study is conducted using Abaqus software to study the influence that various geometric and material properties have on the capacity of the members. Moreover, the serviceability limit state is also explored through a detailed analysis of the deflection behaviour.